Does Month of Birth affect Individual Health and Educational Attainment in Iceland? - Þórhildur Ólafsdóttir 1973- (2010)
The main objective of this study is to examine whether there is a link between individual month of birth and later outcomes in Iceland. Later outcomes are defined here as self-assessed health and years of schooling. In previous research from social and natural sciences, month of birth has been proposed as an early determinant of adult outcomes. In an attempt to explain such an association, different theories have emerged. Some include effects as early as before conception pointing towards the importance of family background, particularly mother characteristics, as a causal factor for variations in outcomes by month of birth. Specifically, the results from the current study indicate whether future study within the Icelandic population should focus on a possible effect of family background on seasonality of outcomes by month of birth. Furthermore, the results have implications for previous studies regarding the effects of different schooling systems, the relative age effect and the use of month of birth as an instrumental variable (IV) for educational duration in two-stage estimations. The case of Iceland is interesting in this regard since a difference in mandatory schooling by month of birth does not exist in Iceland as in the United States. Thus, if the hypothesized reason that the compulsory schooling laws in the U.S. explain variations in years of schooling by month of birth, are true, one would expect different results when examining this relationship within the Icelandic cultural and institutional setting. The data originates from a postal survey, which includes a random sample of 20,000 Icelandic women aged 18-45. Regression methods are used to estimate whether month of birth is associated with self-assessed health and years of schooling. The results do not confirm an association between month of birth and self-assessed health and years of schooling at traditional levels of significance. However, in previous studies, the measured association of month of birth and years of schooling is small and if one ...